“The more things change the more they stay the same”: Decision-making in Zimbabwean transnational families - Chereni, Admire (Migration Letters, 2014)
Whereas studies have documented socio-cultural changes connected to migration dynamics, there is a dearth of knowledge about decision-making in transnational families. This article seeks to understand transformations in decision-making in six Zimbabwean transnational families. This is done by examining qualitative data generated through semi-structured interviews with members of the migrant families. While accentuating the need for more research on interpersonal processes in transnational families, the article illustrates that shifts in gender roles may occur alongside gender-normative behaviours that maintain women in subordinate decision-making roles.